Clinical role of 18F-FDG-PET/CT in the assessment of suspected recurrent gastric cancer after initial surgical resection: is there any effect of FDG-PET/CT in patients' management? - Bilici, Ahmet Erkan; Şeker, Mesut; Öven Ustaalioğlu, Bala Başak; Aslan Canpolat, Nesrin; Tekinsoy, Bülent; Salepçi, Taflan; Gümüş, Mahmut (Oxford University Press, 2010)
[Abstract Not Available]
Keywords: FDG; PET/CT; Gastric Cancer; Surgical Resection